Intellegent computers − the means for automatization of scientific investigating and reliable solving of scientific and engineering problems - Molchanov, I.N.; Khimich, A.N.; Popov, A.V.; Chistyakova, T.V.; Yakovlev, M.F. (Искусственный интеллект, 2014)
The intelligent computer investigates characteristics of problem’s computer model and on the basis of this
information it automatically constructs the solution algorithm, forms a topology from MIMD-computer’s
processors, creates a parallel program code, solves the problem and, finally, estimates the reliability of the
obtained results (the proximity between machine and mathematical solutions as well as estimate of inherited
error in the obtained solution). Інтелектуальний комп’ютер досліджує властивості комп’ютерної моделі задачі і на підставі цієї
інформації автоматично будує алгоритм рішення, формує топологію з процесорів MIMD-комп’ютера,
створює код програми паралельних обчислень, вирішує завдання і по закінченні рахунки оцінює
достовірність отриманих результатів (близькість машинного рішення до математичного та оцінку
спадкової похибки в отриманому рішенні). Интеллектуальный компьютер исследует свойства компьютерной модели задачи и на основании этой
информации автоматически строит алгоритм решения, формирует топологию из процессоров MIMD-
компьютера, создает код программы параллельных вычислений, решает задачу и по окончании счета
оценивает достоверность полученных результатов (близость машинного решения к математическому и
оценку наследственной погрешности в полученном решении).